Deep-insights: Nanoengineered gel-based localized drug delivery for arthritis management - Anitha Sriram; Harshada Ithape; Pankaj Kumar Singh (Asian Journal of Pharmaceutical Sciences)
Arthritis is an inflammatory joint disorder that progressively impairs function and diminishes quality of life. Conventional therapies often prove ineffective, as oral administration lacks specificity, resulting in off-target side effects like hepatotoxicity and GIT-related issues. Intravenous administration causes systemic side effects. The characteristic joint-localized symptoms such as pain, stiffness, and inflammation make the localized drug delivery suitable for managing arthritis. Topical/transdermal/intra-articular routes have become viable options for drug delivery in treating arthritis. However, challenges with those localized drug delivery routes include skin barrier and cartilage impermeability. Additionally, conventional intra-articular drug delivery also leads to rapid clearance of drugs from the synovial joint tissue. To circumvent these limitations, researchers have developed nanocarriers that enhance drug permeability through skin and cartilage, influencing localized action. Gel-based nanoengineered therapy employs a gel matrix to incorporate the drug-encapsulated nanocarriers. This approach combines the benefits of gels and nanocarriers to enhance therapeutic effects and improve patient compliance. This review emphasizes deep insights into drug delivery using diverse gel-based novel nanocarriers, exploring their various applications embedded in hyaluronic acid (biopolymer)–based gels, carbopol-based gels, and others. Furthermore, this review discusses the influence of nanocarrier pharmacokinetics on the localization and therapeutic manipulation of macrophages mediated by nanocarriers. The ELVIS (extravasation through leaky vasculature and inflammatory cell-mediated sequestration) effect associated with arthritis is advantageous in drug delivery. Simply put, the ELVIS effect refers to the extravasation of nanocarriers through leaky vasculatures, which finally results in the accumulation of nanocarriers in the joint cavity.